2018
DOI: 10.1108/bfj-09-2017-0502
|View full text |Cite
|
Sign up to set email alerts
|

Examining consumer attitudes toward genetically modified and organic foods

Abstract: Purpose The purpose of this paper is to examine consumer attitudes toward genetically modified (GM) and organic foods with a broader list of control variables that includes green attitudes, impulsive purchasing, concerns about privacy, religiosity, birth order, and political preferences. Design/methodology/approach US internet panelists were asked about their preferences for purchasing non-GM produce, non-GM cereal, and organic products even if they cost a little more. They were also asked if genetically eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 80 publications
2
38
3
1
Order By: Relevance
“…This gap could be due to a lack of objective knowledge prevalent among the average consumer (McFadden and Lusk, 2016) as well as the negative perception of the first generation of GE technologies, such as golden rice, which contains higher levels of Vitamin A due to genetical modification and that studies found to be perceived as unnatural and risky (e.g. Wesseler and Zilberman, 2014;Larson, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This gap could be due to a lack of objective knowledge prevalent among the average consumer (McFadden and Lusk, 2016) as well as the negative perception of the first generation of GE technologies, such as golden rice, which contains higher levels of Vitamin A due to genetical modification and that studies found to be perceived as unnatural and risky (e.g. Wesseler and Zilberman, 2014;Larson, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Overreporting was found for voting, exercise, seat belt use, having a library card, and energy conservation. More recent examples of SDB effects include the overstatement of incomes by some Danish respondents, the inflation of interest in buying organic food, and a contribution toward the survey errors in the 2016 U.S. presidential election (Brownback & Novotny, 2018; Hariri & Lassen, 2017; Larson, 2018).…”
mentioning
confidence: 99%
“…Deciding on organic food enables both upgraded environmental effect and enhanced nutritional consequences (25). Environmentally friendly attitudes are positively related to non-genetically modified and organic food ones (26). Sustainable consumption may comprise both sustainable principles and sustainable actions (27).…”
Section: Consumers' Perceptions Beliefs and Trust Of The Quality Fementioning
confidence: 99%